Trend analysis of precipitation data in flood source areas of Kelantan River Basin, Malaysia - Abdulkareem, Jabir Haruna; Sulaiman, Wan Nor Azmin (2015)
Using the data of annual maximum series of 24-hour precipitation and the annual maximum flood (AMF) from Kelantan, the time series analysis of the river basin was analyzed for possible trend. The purpose of this study is to investigate the variability of precipitation in flood source areas of Kelantan river basin by detecting precipitation changes in the temporal structure for the period 1984-2014. Three rain gauge stations located upstream of the river basin (Jeli, Kuala Krai and Brook) were selected to represent the flood source areas where the annual maximum series of 24-hour precipitation data were taken. For the AMF data, four discharge gauging stations were selected (Kuala Krai, Galas, Pergau and Nenggiri) for analysis. Mann-Kendall and Sen slope estimator non-parametric tests were adopted for the methodology in order to detect possible precipitation trend. The application of this methodology resulted in the detection of no statistically significant trend in the annual maximum series of 24-hr precipitation in all the selected locations for the past 31 years. Whereas, the AMF series signalled significance at 5% level in all the stations where the AMF data was taken. This might be as a result of watershed characteristics such as land use changes, soil, topography that occurred in the study area which needs to be studied.